Comparative Genomics - Xia, Xuhua; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2013)
This book provides an evolutionary conceptual framework for comparative genomics, with the ultimate objective of understanding the loss and gain of genes during evolution, the interactions among gene products, and the relationship between genotype, phenotype and the environment. The many examples in the book have been carefully chosen from primary research literature based on two criteria: their biological insight and their pedagogical merit. The phylogeny-based comparative methods, involving both continuous and discrete variables, often represent a stumbling block for many students entering the field of comparative genomics. They are numerically illustrated and explained in great detail. The book is intended for researchers new to the field, i.e., advanced undergraduate students, postgraduates and postdoctoral fellows, although professional researchers who are not in the area of comparative genomics will also find the book informative.
Preface -- Acknowledgments -- Chapter 1.What is Comparative Genomics? -- Chapter 2.Comparative Genomics and the Comparative Methods -- Chapter 3.Comparative Viral Genomics: Detecting Recombination -- Index.
Keywords: Life sciences; Molecular ecology; Evolution (Biology).; Microbial genetics; Animal genetics; Life Sciences; Evolutionary Biology; Molecular Ecology; Mathematical and Computational Biology; Microbial Genetics and Genomics; Animal Genetics and Genomics